Pengabdian Masyarakat Melalui Sosialisasi Prosedur Karantina Mandiri Di Puskesmas Tiban Baru Dan Masyarakat Sekitar Perumahan Mahasiswa Atau Mahasiswi Kota Batam - Delladari Mayefis; Arie Vonikartika; Diani Mega Sari; Rury Trisa Utami (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Firstly, COVID-19 was reported in Indonesia on March 2, 2020, in several cases. The latest data on April 23 2020, there were 15,331 confirmed cases with 120 deaths. COVID-19 cases in Batam City have started to increase in the last week. As of April 30, there have been five positive cases of COVID-19, and one person died. Tiban Baru is one of the area in the Batam City. Many people still do not understand self-isolation, especially when they have a history of contact with positive cases, have just returned or traveled outside the city, and have symptoms similar to COVID-19. Furthermore, they are still in contact with other family members. This will certainly expand the expansion of case transmission in households. This activities partner up with a village headman of Tiban Baru. The solution to the problem is education to the public about self-isolation for people in the assesment in handling COVID-19. Educations provided through the media of leaflets and masks donations to people affected by COVID-19. The purpose of this activity is to increase public knowledge about self-isolation efforts if they have symptoms similar to COVID-19 or contact with COVID-19 cases and improve hygiene in the community as an effort to prevent transmission of COVID-19